Structures and optical properties of solid hydrogen at ultrahigh pressures: High-Pressure Studies - Nagara, Hitose (ФІЗИКА НИЗЬКИХ ТЕМПЕРАТУР, 2003)
We have studied the electronic energy bands for the structures whose primitive cell contains up to four molecules, with full optimization of the structures, based on the GGA and LDA band calculations. Above 250 GPa, the eventual optimal structure obtained by the GGA or the LDA calculation is Cmca, which is a layered structure with the molecular bonds lying in planes, and has a metallic band structure with no band gaps. The metallic property of the band structure still remains unchanged even if the molecular bonds in the plane of the Cmca were inclined such that the atoms in the molecule escape from the plane. The electronic bands of the Cmca and those of some other candidate structures are discussed in the light of recent experimental result. Effects of the occupation of electronic states on the predicted optimal structures are also studied.